Первоклассница: повесть / Е. Л. Шварц ; худож. Е. М. Володькина - Шварц Евгений Львович (Детвора, 2011)
1-3кл Экземпляры: Ф 4 / Д (20180625) / Инвентарный номер: 80328 / Цена: 183.38 / Сис.шифр: 84(2Рос-Рус)6-4 / Авт.знак: Ш 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)6-4